Little change in tobacco imagery on New Zealand television: 10 years on. (June 2016) - Marsh, Louise; McGee, Rob; Robertson, Lindsay; Ward, Matthew; Llewellyn, Rebecca
Abstract: Objectives: To examine changes in the frequency and contexts of tobacco imagery on New Zealand television since 2004. Methods : A content analysis of 73 hours of prime time evening television in 2014, including programs, advertisements and trailers, was coded for tobacco imagery. Imagery was defined as being either neutral/pro‐tobacco or anti‐tobacco. Results : Of the 93 programs coded, 29% had at least one scene with tobacco imagery. Of the 71 scenes with tobacco imagery, 59 were judged as showing neutral/pro‐tobacco imagery, while 12 showed anti‐tobacco imagery. No significant change in the number of programs containing tobacco imagery, or the type of imagery, was found since 2004, but there were fewer scenes that contained imagery. Conclusions : There has been little change in the amount of tobacco imagery over the past decade. Given the potential for tobacco imagery to promote smoking among young people while reinforcing the habit among those who are trying to quit, action needs to be taken. Implications : More could be done to counterbalance pro‐tobacco imagery by promoting the Quitline and anti‐tobacco media campaigns, and encouraging producers of local TV programs to consider the depiction of tobacco imagery in a way that reflects declining tobacco use.